Entre essence et existences: les identités classique et moderne de l'Europe - Bernard, Guillaume (2010)
Abstract: It seems possible to distinguish a traditional design and a modern vision from Europe, the first resting on an ontology, the second on a phenomenological construction. Traditional Europe is the incarnation of a culture in a geographically variable space, territories being able to be gained or lost. In this design, the identity of Europe is determined by its elements founders who gave him its unit. Contrary, since the modern society is the result of a contract, the European Union wants to be detached of any ontological identity. Moreover, whereas in the Roman and medieval tradition, the empire was a qualitative and spiritual concept, this one rocked in the reign of the quantity. Consequently, the territorial extent of the European Union, in the modern thought, is only limited by the wills